The use of priming and body of the brand in the media as one of the types of marketing techniques. - Урузбаева, Н. А.; Пак, Э. Ю. (Journal of Economic Research & Business Administration, 2015)
Taking into account the emergence of a large number of channels, we can say that a lot of competition increases. In this connection, and increases the need to introduce in the marketing channels. And concepts such as priming and telebrend make it possible to increase channel rating, which is an important factor for advertisers.